Intelligent Decision Technologies 2017 Proceedings of the 9th KES International Conference on Intelligent Decision Technologies (KES-IDT 2017) - Part I (Cham : Springer International Publishing, 2018)
The volume presents a collection of peer-reviewed articles from the 9th KES International Conference on Intelligent Decision Technologies (KES-IDT-17), held in Vilamoura, Algarve, Portugal on 21-23 June 2017. The conference addressed critical areas of computer science, as well as promoting knowledge transfer and the generation of new ideas in the field of intelligent decision making, project management and data analysis. The range of topics addressed includes methods of classification, prediction, data analysis, decision support, modeling, social media and many more in such diverse areas as finance, linguistics, management and transportation.
The Shapley Value and Consistency Axioms of Cooperative Games under Incomplete Information -- Patients' EEG Data Analysis via Spectrogram Image with a Convolution Neural Network -- Decremental Subset Construction -- Incremental GEP-Based Ensemble Classifier -- Applying the Intelligent Decision Heuristic to Solve Large Scale Technician and Task Scheduling Problems -- Manipulability of Majority Relation-Based Collective Decision Rules -- Dispersed System with Dynamically Generated Non-disjoint Clusters - Application of Attribute Selection -- Evaluating Importance for Numbers of Bins in Discretised Learning and Test Sets -- Heuristic Method of Air Defense Planning for an Area Object with the Use of Very Short Range Air Defense -- Tips Service and Water Diary an Innovative Decision Support System for the Efficient Water Usage at Households -- A Macroeconomic Model for Service Science Capitalism: Thetical and Antithetical Economics -- Managerial Decisions Modelling for the Company Development Strategy -- Super Pairwise Comparison Matrix in the Dominant AHP with Hierarchical Criteria.
Engineering
text file PDF
Keywords: Computational intelligence; Artificial intelligence